The Correlation Between Students’ Anxiety and Learning Activity towards Their Speaking Ability - Mira Listia Julianingsih (Universitas Pendidikan Mandalika, 2018)
This research was aimed to know the correlation between students’ anxiety and learning activity towards their speaking ability at tSMAN 01 Jereweh in academic year 2016/2017. This research was correlation research The sample of the research was all of the second grade students of SMAN 01 Jereweh in academic year 2016-2017 which consists of one class. One class was 28 students. The data was collected by using questionnaire to collected the data of students’ learning activity and their anxiety meanwhile test to know student speaking ability speaking test was administered. The data was analyzed by using person product moment, multiple linear regression and multiple correlation. From the data analysis, it was found that the result of correlation score r=0.687. It means the correlation between both of variable and Y in moderate correlation because “r” score not close enough to +1. And the significant score f=9,523 it mean f=test > f-table of on degree of freedom of 25. Based on the result of the study, in can be concluded there is the the correlation between students’anxiety and learning activity towards their speaking ability at the second grade student of SMAN 01 Jereweh in academic year 2016/2017. It means that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected.